Do exercise-based prevention programs reduce injury in endurance runners? A systematic review and meta-analysis - Wu, H.; Brooke-Wavell, K.; Fong, D. T. P.; Paquette, M. R.; Blagrove, R. C. (Sports Medicine, 2024)
Background: Endurance running is a popular sport and recreational activity yet is associated with a high prevalence of injury. Running related injuries (RRIs) are a leading cause of drop-out and represent a substantial financial burden to runners and healthcare services. There is clear evidence for the use of exercise-based injury prevention programs in games-based and youth sport settings, yet the research investigating the use of exercise to reduce injury risk in endurance runners has not been adequately reviewed recently. Objectives: The aim of this review and meta-analysis was to systematically summarize the current research that has investigated the effect of exercise-based prevention programs and their state of supervision on the risk of RRIs in endurance runners. Methods: Three databases were searched for relevant studies. Selection and review were completed by two independent reviewers using the following inclusion criteria: (1) study population used endurance running training for health, occupational, or performance outcome(s); (2) participants performed running as their main form of exercise (> 50% of their total training time); (3) study was a randomized controlled trial; (4) a non-running-based exercise intervention was used; (5) a running-only or placebo exercise control group was included; (6) injury rate or incidence was reported; (7) injuries were recorded prospectively alongside the exercise training. Two meta-analyses were conducted using random-effects models, one based on log risk ratio and one based on log incidence rate ratio. The Cochrane Risk of Bias Assessment Tool 2 was used to evaluate the quality of studies and the Grading of Recommendations Assessment, Development and Evaluations approach was employed to grade the certainty of evidence. Results: A total of nine articles containing 1904 participants were included in analysis. Overall pooled results showed no significant differences between intervention and control groups in injury risk (z = - 1.60; p = 0.110) and injury rate (z = - 0.98; p = 0.329), while a post hoc analysis evaluating supervised interventions only showed that injury risk was significantly lower in the intervention group compared to the control group (z = - 3.75, p < 0.001). Risk of bias assessment revealed that seven studies included in the analysis were of low quality. Conclusions: Exercise-based interventions do not appear to reduce the risk and rate of running-related injuries. Supervision may be essential for exercise-based intervention programs to reduce risk of RRIs, possibly due to increased compliance. Studies with more robust designs that include supervised exercise interventions should be prioritized in the future.